Matrix metalloproteinases and their tissue inhibitors as novel markers in invasive pituitary adenomas - a review - Joanna Szydełko; Michał Litwińczuk; Magdalena Szydełko (Kazimierz Wielki University, 2019)
Introduction: Pituitary adenomas are generally benign central nervous system neoplasms with still increasing prevalence, especially in younger people. According to the recent data, approximately 30-45% of them invade the local structures, which make their total resection impossible and result in high recurrence rate. Despite the huge advances in management with pituitary tumors, there are no universal biomarkers predicting their course. That is why, the two-way relationship between matrix metalloproteinases (MMPs) activities and the microenvironment of pituitary adenomas is an important object of extensive studies. Aim of the study: This article summarizes the current knowledge about selected MMPs and their tissue inhibitors (TIMPs) in tumorigenesis of pituitary adenomas as well as their role in local invasion in different hormonally active and inactive pituitary tumors. Description of knowledge: MMPs are a family of zinc-dependent proteolytic enzymes, which are engaged in various physiological and pathological conditions. So far, their role in different malignancies have been known for many years. Nevertheless, the possible effects of MMPs and TIMPs in pituitary adenomas are not fully understood. Recent studies suggested that MMPs' expression is significantly higher in invasive pituitary tumors as compared to non-invasive pituitary adenomas, while the expression of TIMPs is decreased, which may prove their involving in tumorigenesis. Conclusions: MMPs may be predictive factors of the invasiveness and the higher recurrence rate in the group of patients with pituitary adenomas. Understanding the changes in the MMPs-TIMPs system and discovering of its exact mechanisms may result in applying novel screening options as well as modifying diagnostic process and treatment scheme. Therefore, further researches are required to determine the effects of MMPs and TIMPs and their role in the pathogenesis of invasive pituitary tumors.